Marketing Strategy for Orchestral Music Concerts as a Tool for Forming an Arts Community - Kustedja, Elaine V.B.; Respati, Yacobus Ari; Wiriadisastra, Fauzie; Prasiwi, Intan Mareta (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
This study explores the potential for a community-building process by using marketing techniques to plan an orchestra performance in Bandung. Under the University's sponsorship, the Parahyangan Orchestra (Parchestra), an orchestral music community, is organizing this orchestra event. In addition to being analyzed from a sociological standpoint, the presentation of the correlation of community building also intersects with Parchestra's marketing beliefs and techniques. The research method employed was qualitative, with an internal comparative study approach to two concerts held in 2023. Data were gathered through interviews and documented observations. Based on the findings of the study, Parchestra may be able to interact with stakeholders in order to learn about each other's expectations. One of the keys to building a great community is to learn about the audience's expectations as well as its internal management. However, the focus of this research is on the interaction between Parchestra and its audience. Thus, more investigation is required to look at the viewpoint of other interested parties. Contribution: The research incorporates a sociological perspective, examining how community dynamics influence and are influenced by cultural events. This intersection of sociology and marketing provides a richer understanding of how orchestras can connect with their audiences and stakeholders, thereby enhancing the overall cultural experience.